Issues and sources in spanish language TV: a comparison of Noticiero Univisión and NBC Evening News - Lozano, José Carlos (Frontera Norte, 2017)
El artículo presenta los resultados de un análisis de contenido sobre los temas y las fuentes informativas incluidas en el noticiero Univisión y los compara con el contenido del programa noticioso nocturno de la cadena NBC. El autor concluye que no hay diferencias radicales entre uno y otro programas en temas y enfoques, y que el noticiero Univisión proporciona mayor acceso a fuentes informativas anglosajonas que hispanas. En el plano nacional, el noticiero en español brinda la mayor parte de su tiempo a funcionarios gubernamentales anglosajones del más alto nivel, y difunde las noticias desde Washington y Nueva York, no desde las ciudades norteamericanas con mayor número de habitantes hispanos. En la información internacional, el noticiero Univisión -aunque dedica mayor tiempo que NBC a este renglón- parece reproducir la tendencia típica de subrayar accidentes y violencia en el Tercer Mundo, especialmente en Latinoamérica. ABSTRACT This article presents the findings of a comparative study of the topics and the information sources of two TV news broadcasts: the NBC Evening News and the Spanish-language news program, Univisión. It shows that there are no major differences between them in terms of the topics and the approaches followed, and that Univisión bases its reporting on Anglo-Saxon information sources rather than Hispanic ones.In national news, the Spanish language broadcast devotes most of its time to high-ranking government officials and gathers its information in Washington and New York, not in the U.S. cities with the largest Spanish-speaking populations. On the international scene, even though Univisión gives more time to this area than does NBC it still follows the English-language network's tendency to emphasize incidents and violence in the Third World, specifically in Latin America, over other news.1